THE RELATIONSHIP BETWEEN LEARNING STYLES AND ACADEMIC PERFORMANCE AMONG UNIVERSITY STUDENTS: A STUDY OF AMERICAN DEGREE TRANSFER PROGRAM STUDENTS IN STEM AND NON-STEM MAJORS USING VERMUNT’S INVENTORY LEARNING STYLES (ILS) - LIM YOU PING, LOH KAH HENG, THERESA CHIEW GIM EAN, TEH E-YANG, NG ENG HUI, YAP JIA HUI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Globalization and increased mobility in higher education have diversified the student demographics, learning expectations and preferences, thereby influencing their academic performance, motivation, and career readiness. Divergent cognitive and academic demands in STEM and non-STEM fields further shape students’ engagement and learning approaches. As traditional pedagogy is ineffective to address diverse needs, responsive teaching is vital to enhance learning outcomes. However, there is notable lack of research that simultaneously explores the diverse learning styles across multiple disciplines, highlighting the need to examine learning styles and correlation with academic performance in STEM and non-STEM contexts. This study employs the widely recognized Vermunt’s Inventory Learning Styles (ILS) model as a guiding framework. By identifying and addressing learning styles, educators can design more inclusive teaching strategies in shaping a student educational journey and foster long-term broader development in a diverse and interdisciplinary university settings. Statistical results reveal no significant differences in the four core learning dimensions: process strategies, regulation strategies, learning orientations and mental model of learning across academic disciplines. However, STEM students scored significantly higher in the directed learning sub-components: deep processing, self-regulation and constructivist view. Statistical results showed a significant difference in the high adaptiveness sub-category: meaning-directed learning style. Correlation analysis showed no significant positive relationship between CGPA and learning styles among STEM and non-STEM students. Overall, the data supports the research outcome that learning environments can influence style development, and that promoting meaning-directed strategies across all disciplines could enhance academic engagement and performance.